The ADRB3 rs4994 polymorphism increases risk of childhood and adolescent overweight/obesity for East Asia's population: an evidence-based meta-analysis. (1st January 2020) - Xie, Chenyao; Hua, Wenxi; Zhao, Yuening; Rui, Jingwen; Feng, Jiarong; Chen, Yanjie; Liu, Yu; Liu, Jingjing; Yang, Xiaoqin; Xu, Xiaojing
ABSTRACT: Whether the Adrenoceptor Beta 3 ( ADRB3 ) gene rs4994 polymorphism could affect the individual risk of childhood and adolescent overweight/obesity remains controversial. This meta-analysis was performed to estimate the prevalence of this polymorphism in overweight/obesity, and test the potential association by summarizing existing evidence. Comprehensive literature search in PubMed, Web of Science, Cochrane Library, Wanfang, and CNKI databases was performed to identify eligible data sets. Finally, 16 studies involving 5, 147 overweight/obese cases and 7, 350 non-obese controls were included for further synthetic analyses. Odds ratio (OR) and its corresponding 95% confidence intervals (CIs) were statistically calculated. Totally, 69.9% of the included subjects came from East Asia. In the meta-analysis for overall population, statistically significant associations with increased risk of childhood and adolescent overweight/obesity were identified in allele model (OR 1.23, 95% CI 1.10–1.38), heterozygote model (OR 1.39, 95% CI 1.16–1.68), and dominant model (OR 1.31, 95% CI 1.12–1.54). Further stratified analysis according to geographical regions revealed that the statistical significance could only be detected in the East Asia subgroup in allele model, homozygote model, heterozygote model, and dominant model. In summary, our meta-analysis indicated that the ADRB3 rs4994 polymorphism could significantly increase the risk of childhood and adolescent overweight/obesity, especially for the East Asia's population.